Application of salting-out assisted liquid-liquid extraction for the determination of oxytetracycline, tetracycline, tilmicosin, and tylosin in cow milk by liquid chromatography with photodiode array detection - Jalal Hassan; Gholam-Reza Shams; Mostafa Pourrastegar; Ali Pourshaban-Shahrestani (MethodsX, 2024)
This paper introduces a novel, sensitive, and rapid method for the quantification of oxytetracycline, tetracycline, tilmicosin, and tylosin residues in cow's milk. The method involves a two-step process of extraction and detection. The extraction process uses acetonitrile and salting-out assisted liquid-liquid extraction to isolate the antibiotics from the milk. The detection process employs Liquid Chromatography coupled with photo-diode array detector (PDA) to quantify the antibiotics. The method has been successfully applied to milk samples, demonstrating its effectiveness and potential for widespread use in residue analysis. • The calibration curves for the antibiotics were found to be linear within the range of 0.06–3.0 µg/mL to 0.1–3.0 µg/mL. • The limits of detection for oxytetracycline, tetracycline, tilmicosin, and tylosin were 0.03 µg/mL, 0.02 µg/mL, 0.04 µg/mL, and 0.02 µg/mL respectively. • The method demonstrated an average recovery rate of over 90% from milk samples with peak values reaching up to 0.100–0.200 µg/mL.